Developing Teaching Materials for Creative Writing in English Language Poetry Based on Molucan Archipelago at English Education Study Program FKIP Unpatti - Binnendyk, Sophia; Que, Stella Rose (MATAI: International Journal of Language Education, 2023)
The aims of this research are 1) to examine the theoretical try out of the developed materials, 2) to examine learners’ attitude towards the developed materials, 3) to examine the effectiveness of the developed materials. The approach and research method for developing Creative Writing Poetry teaching materials used Borg and Gall's development research steps which consisted of 10 steps. However, because this study was small, Borg and Gall suggested limiting the research to a small scale. The instrument in this research is the attitude & content instrument. The rubric used for the assessment of creative writing of poetry consists of four categories, namely meaning and originality, sensory details, form, and grammar. Based on the results of the operational trial of 20 students, it turned out that their scores were in the range of 'good' and 'very good categories. Thus, it can be concluded that the Creative Writing Poetry with Moluccas Content teaching materials effectively can develop students' creativity of writing.